2016
DOI: 10.1016/j.chemgeo.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid lithospheric thinning of the North China Craton: New evidence from cretaceous mafic dikes in the Jiaodong Peninsula

Abstract: The North China Craton is a classic case for the destruction of an ancient craton, in that it records the loss of more than 100 km of ancient refractory lithospheric mantle during the late Mesozoic and early Cenozoic. However, the mechanisms for this lithospheric thinning remain controversial in large part due to the lack of any systematic investigations of the Mesozoic asthenospheric mantle via its derived mafic rocks, which are key to understand the thinning processes. In this paper, we present detailed zirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 100 publications
0
29
0
Order By: Relevance
“…123-121 Ma) (Ma et al, 2014(Ma et al, , 2016. Those intermediate-felsic dikes studied here are mainly oriented to the N, the NNE, and the NNW in the Jiaobei terrain and to the E, the NE, and the NEE in the Sulu orogenic belt (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 85%
See 3 more Smart Citations
“…123-121 Ma) (Ma et al, 2014(Ma et al, , 2016. Those intermediate-felsic dikes studied here are mainly oriented to the N, the NNE, and the NNW in the Jiaobei terrain and to the E, the NE, and the NEE in the Sulu orogenic belt (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…Mesozoic intrusions in the Jiaodong Peninsula can be divided into four suites: (1) the Late Triassic syenite, such as Jiazishan intrusion, which is only found in the easternmost Jiaodong Peninsula (215-209 Ma, LA-ICP-MS zircon U-Pb age, Chen et al, 2003); 2 (Fig. 1b) (Tan et al, 2008;Liu et al, 2009;Cai et al, 2013, A C C E P T E D M A N U S C R I P T 8 2015; Ma et al, 2014Ma et al, , 2016Deng et al, 2017;Liang et al, 2017). Two types of mafic dike have been identified, those derived from enriched lithospheric mantle (arc-like type with enrichment in LILE and LREE but depletion in HFSE; 130-110 Ma) (Liu et al, 2009;Cai et al, 2013Cai et al, , 2015Ma et al, 2014;Deng et al, 2017;Liang et al, 2017) and those derived from asthenospheric mantle (OIB-like type with no depletion in HFSE and enrichment in LREE;…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Liang et al () studied four Early Cretaceous mafic dikes aged at ~126 Ma in south‐eastern Jiaolai Basin and found that those mafic dikes resemble the ARC‐like dikes in Jiaodong Peninsula (Cai et al, ; Guo, Fan, Wang, & Zhang, ; Liu et al, ; Tan et al, ). OIB‐like mafic rocks were locally found in north‐west Jiaodong Peninsula (L. Ma et al, ; L. Ma et al, ). As for the peridotite rocks, there are plenty of mafic‐ultramafic rock lenses in Sulu orogenic belt, including Qianliyan Uplift (S. Chen, Yang, & Li, ; S. Z. Chen et al, ; Ying, Zhang, Kita, Morishita, & Shimoda, ; R. Y. Zhang & Liou, ; J. P. Zheng et al, ), which might provide peridotite spinel grains for Laiyang Group in Lingshan Island.…”
Section: Discussionmentioning
confidence: 99%